Pengaruh Live TikTok, Konten Viral, dan FOMO terhadap Pembelian Kuliner di Jombang - Novia Tri Hidayanti; Kusna Djati Pratama (Jurnal Manajemen Riset Inovasi, 2026)
This study investigates the impact of TikTok Live, viral content, and Fear of Missing Out (FOMO) on the purchasing decisions of Gen Z consumers in Jombang City for food and drink products. Social media, particularly TikTok, has rapidly expanded and functions as a potent digital marketing instrument. It influences consumer behavior through live broadcasting and the dissemination of viral content. The objective is to examine the influence of these three factors on purchasing decisions. This study employs a quantitative methodology. The data was obtained from surveys administered to 60 Gen Z participants who purchased food or beverages following exposure to TikTok advertising. Samples were selected by purposive sampling. Data were examined using multiple linear regression with SPSS software. Findings indicate that TikTok Live exerts a favorable and substantial impact on purchasing decisions. Viral material exerts no substantial impact. FOMO exerts a detrimental and substantial impact. The results indicate that TikTok live streaming effectively enhances consumer purchases, especially within the food industry.